Network meta-analysis of nine large cardiovascular outcome trials of new antidiabetic drugs. Issue 3 (June 2019) - Alfayez, Osamah M.; Al Yami, Majed S.; Alshibani, Mohannad; Fallatah, Saad B.; Al Khushaym, Nasser M.; Alsheikh, Razan; Alkhatib, Nimer
Highlights: GLP-1 receptor agonists showed CV benefit compared to placebo. SGLT-2 inhibitors resulted in a significant reduction in heart failure hospitalizations. DPP-4 inhibitors are comparable to placebo in terms of CV safety. The NMA showed no significant differences among the medications of each class. Abstract: The aim of this network meta-analysis (NMA) was to indirectly compare the cardiovascular (CV) safety of new antidiabetic medications in patients with type 2 diabetes mellitus (T2DM). Data synthesis: A search of the Embase and MEDLINE databases was conducted systematically to identify cardiovascular outcome trials (CVOTs) of new antidiabetic medications (DPP-4 inhibitors, GLP-1 agonists and SGLT-2 inhibitors) in patients with T2DM. The primary outcomes were the composite endpoint of CV death, nonfatal MI, and nonfatal stroke (MACE), death from CV causes, nonfatal MI, nonfatal stroke and death from any cause. Hospitalization for HF and unstable angina were evaluated as secondary endpoints. A total of 9 trials, including 87, 162 patients, met the eligibility criteria and were retained for the analysis. The NMA results showed no significant differences among the DPP-4 inhibitors (sitagliptin, alogliptin, and saxagliptin) in any of the CV endpoints. Similarly, no significant changes were seen in the NMA among the GLP-1 receptor agonists nor the SGLT-2 inhibitors. The pairwise meta-analysis showed that DPP-4 inhibitors have a CV safety profiled comparable to placebo. GLP-1 agonists on the other hand, showed significant reduction in MACE (RR 0.92; 95% CI 0.87–0.97), death from CV causes (RR = 0.88; 95% CI 0.80–0.97), and death from any cause (RR = 0.89; 95% CI 0.82–0.96). SGLT-2 inhibitors showed significant reduction in hospitalization for heart failure events (RR 0.72; 95% CI 0.6–0.86) compared to placebo. Conclusion: This meta-analysis has shown that new antidiabetic medications do not impose any additional CV risk. The indirect comparison among the medications of each class resulted in no significant changes regarding CV endpoints and death from any cause.